Pengaruh Gaya Kepemimpinan Transformasional dan Tranksaksional Terhadap Kinerja Sistem Jaminan Halal HAS 23000 - Yanthy, Evy; Purwanto, Agus; Pramono, Rudy; Cahyono, Yoyok; Asbari, Masduki (BISNIS, 2020)
This study aims to analysis of transformational and transactional leadership styles and their effects on the performance of the HAS 23000 Halal Assurance System implementation in the food industry in Tangerang. The respondents of the study was employees in several food industries that were located in the Tangerang  who had implement the HAS 23000 Halal Assurance System as many as 200 employees and data collection methods by giving online electronic questionnaires to 2000  employees randomly. The analytical tool used in this study is the SEM (Structural Equation Model) on the LISREL program version 8.70. This study provides results that show that transformational leadership style has a positive and significant effect on the performance of the HAS 23000 Halal Assurance System implementation and the transactional leadership style is also positive and affects the performance of the HAS 23000 Halal Assurance System implementation and concluded that leadership is important in the performance of the HAS Halal Assurance System implementation HAS 23000